Hypoglycaemia represents a clinically significant manifestation of PIK3CA‐ and CCND2‐associated segmental overgrowth. Issue 3 (5th February 2018) - McDermott, J.H.; Hickson, N.; Banerjee, I.; Murray, P.G.; Ram, D.; Metcalfe, K.; Clayton‐Smith, J.; Douzgou, S.
Abstract : The PI3K‐AKT signalling cascade has a highly conserved role in a variety of processes including cell growth and glucose homoeostasis. Variants affecting this pathway can lead to one of several segmental overgrowth disorders. These conditions are genetically heterogeneous and require tailored, multidisciplinary involvement throughout life. Hypoglycaemia is common in other overgrowth syndromes but has been described only sporadically in association with PIK3CA and CCND2 variants. We report a cohort of 6 children with megalencephaly‐capillary malformation (MCAP) and megalencephaly‐polydactyly‐polymicrogyria‐hydrocephalus (MPPH) syndromes who developed clinically significant hypoglycaemia. Based on our findings, we suggest that segmental overgrowth patients should be screened for low blood glucose levels during childhood and there should be early specialist endocrine review in any children who develop hypoglycaemia. Abstract : We report a cohort of 6 children with segmental overgrowth (MCAP and MPPH) who developed clinically significant hypoglycaemia.